1993
DOI: 10.1002/path.1711690408
|View full text |Cite
|
Sign up to set email alerts
|

BCL‐2 expression in adult and embryonic non‐haematopoietic tissues

Abstract: The B-cell leukaemia/lymphoma-2 (bcl-2) proto-oncogene is unusual as its product appears to provide survival advantage to B cells by blocking apoptosis. In this study, the expression of bcl-2 has been examined in normal non-haematopoietic tissues, embryos, and psoriatic skin by immunohistochemical staining. Bcl-2 protein expression is mainly observed in cell populations with a long life and/or proliferating ability such as duct cells in exocrine glands, basal keratinocytes, cells at the bottom of colon crypts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
126
1
5

Year Published

1994
1994
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(143 citation statements)
references
References 11 publications
11
126
1
5
Order By: Relevance
“…In addition to chromosome loss, recent studies disclosed diffuse presence of bcl-2 proto-oncogene expression in SCCs consistent with uncontrolled proliferation in this tumour (Sleater et al, 1994). The same investigation revealed bcl-2 positivity in KAs in the proliferative phase (Sleater et al, 1994), which was limited to the basal cell area, similar to normal epidermis or adnexal epithelium (Lu et al, 1993). In the process of maturation the bcl-2 activity disappears, consistent with the initiation of apoptosis at involution of KAs.…”
Section: Discussionmentioning
confidence: 54%
“…In addition to chromosome loss, recent studies disclosed diffuse presence of bcl-2 proto-oncogene expression in SCCs consistent with uncontrolled proliferation in this tumour (Sleater et al, 1994). The same investigation revealed bcl-2 positivity in KAs in the proliferative phase (Sleater et al, 1994), which was limited to the basal cell area, similar to normal epidermis or adnexal epithelium (Lu et al, 1993). In the process of maturation the bcl-2 activity disappears, consistent with the initiation of apoptosis at involution of KAs.…”
Section: Discussionmentioning
confidence: 54%
“…In contrast to the prolonged cell survival observed when elevations in the levels of Bcl-2 protein are achieved through gene transfer methods, antisense-mediated reductions in bcl-2 gene expression have been shown to accelerate the rate of cell death in the setting of growth factor withdrawal (Reed et al, 1990a,b), thus fulfilling another of Koch's postulates and confirming the importance of bcl-2 in the regulation of cell survival. Antisense experiments have additionally demonstrated that marked reductions in Bcl-2 protein levels, though rendering ceils more prone to apoptosis, are by themselves often insufficient for causing cell death (Reed et al, 1990a,b;Kitada et al, 1993): a finding that is consistent with the observation that several types of cells do not contain detectable Bcl-2 protein in vivo LeBrun et al, 1993;Lu et al, 1993).…”
Section: Bcl-2 Blocks a Final Common Pathway:for Programmed Cell Deathmentioning
confidence: 80%
“…The antiapoptotic Bcl-2 is expressed in undifferentiated keratinocytes, but it is downregulated when the cells leave the basal layer and start to differentiate. 96 Conversely, both proapoptotic Bax and Bak and the antiapoptotic Bcl-X L are expressed in the suprabasal layers of the epidermis. 2,97,98 Abnormalities in skin formation have not been reported for any of the Bcl-2 family member knockouts, 99 except for Bcl-2 knockout mice that have an altered hair follicle cyclus compared to wild-type mice.…”
Section: Mitochondrial Factors and Apoptosome Formationmentioning
confidence: 99%